A Democratic Emergency After a Health Emergency? Exposure to COVID‐19, Perceived Economic Threat and Support for Anti‐Democratic Political Systems. (19th September 2020) - Roccato, Michele; Cavazza, Nicoletta; Colloca, Pasquale; Russo, Silvia
Abstract : Objectives: The urgency of the COVID‐19 pandemic has led governments to impose restrictions on individual freedom and required citizens to comply with these restrictions. In addition, lockdowns related to COVID‐19 have led to a significant economic crisis. We aimed to study how the pandemic and related economic threats have impacted support for anti‐democratic political systems. Method: We analyzed data from a quota panel of the Italian adult population ( N = 1, 195), surveyed once before and once during the pandemic. Results: A hierarchical regression model showed that exposure to COVID‐19 and perceived economic insecurity were associated with support for anti‐democratic political systems, independent of participants' predispositions toward a strong leader. Conclusion: An authoritarian personality is not a necessary precondition for individual anti‐democracy: when facing severe personal threats, anyone could restore a subjective sense of control over the social world by becoming anti‐democratic, independent of their initial predisposition to support anti‐democratic political systems.